2021
DOI: 10.21930/rcta.vol22_num3_art:1920
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento productivo de cuyes (Cavia porcellus L.) en crecimiento suplementados con prebióticos y probióticos naturales

Abstract: La investigación tuvo como objetivo determinar el efecto de los prebióticos y probióticos naturales suplementados en la alimentación, sobre el comportamiento productivo de cuyes en crecimiento. Se emplearon 50 cuyes machos de 14 días de edad, de raza Perú con un peso promedio de 380 g, distribuidos mediante un diseño completo al azar con cinco tratamientos y cinco repeticiones, considerando dos animales por repetición. La fase experimental tuvo una duración de 35 días. Se evaluó: consumo de alimento (g), peso … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The increase in nutrient digestibility could be due to the increased enzyme activity in the gut caused by the administered probiotics [10]. Research has reported increased amylase enzyme activity when Lactobacillus is added to piglets diets [14], and increased sucrase and lactase activity when Lactobacillus is added to pig diets [7].…”
Section: Productive Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in nutrient digestibility could be due to the increased enzyme activity in the gut caused by the administered probiotics [10]. Research has reported increased amylase enzyme activity when Lactobacillus is added to piglets diets [14], and increased sucrase and lactase activity when Lactobacillus is added to pig diets [7].…”
Section: Productive Behaviourmentioning
confidence: 99%
“…Probiotics also have beneficial properties as growth promoters, feed conversion improvers, gut flora modifiers, helping the animal to be more resistant to disease and reducing the use of antibiotics [8,9]. 2 The use of microbial bioactive such as probiotics, prebiotics and symbiotic, emerges as a viable alternative to antibiotic growth promoters [10], with the premise of maintaining meat safety, improving animal welfare, the development of the gastrointestinal tract and the immune system [11], improving carcass yield, without leaving residues in the carcass [12]. Recent studies provide encouraging data on the inclusion of diets with beneficial microorganisms in the ability to balance the microbiota in the different segments of the gastrointestinal tract, which has attracted much attention from researchers [2].…”
Section: Introductionmentioning
confidence: 99%